Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd003772.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for acute pyelonephritis in children

Abstract: These results suggest that children with acute pyelonephritis can be treated effectively with oral antibiotics (cefixime, ceftibuten and amoxycillin/clavulanic acid) or with short courses (2 to 4 days) of IV therapy followed by oral therapy. If IV therapy is chosen, single daily dosing with aminoglycosides is safe and effective. Studies are required to determine the optimal total duration of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 59 publications
1
54
0
7
Order By: Relevance
“…However, a more recent meta-analysis evaluating different antibiotic regimens for acute pyelonephritis in children found that there was no difference in the effectiveness of oral therapy with thirdgeneration cephalosporins compared with amoxicillin-clavulanate. 2 Moreover, third-generation cephalosporins may no longer offer the assured antimicrobial coverage for patients with complicated UTIs that they once did. Lutter et al 21 reported that children receiving antimicrobial prophylaxis with breakthrough UTIs were often infected with an organism resistant to thirdgeneration cephalosporins, despite the fact that none of these children were taking cephalosporin prophylaxis.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a more recent meta-analysis evaluating different antibiotic regimens for acute pyelonephritis in children found that there was no difference in the effectiveness of oral therapy with thirdgeneration cephalosporins compared with amoxicillin-clavulanate. 2 Moreover, third-generation cephalosporins may no longer offer the assured antimicrobial coverage for patients with complicated UTIs that they once did. Lutter et al 21 reported that children receiving antimicrobial prophylaxis with breakthrough UTIs were often infected with an organism resistant to thirdgeneration cephalosporins, despite the fact that none of these children were taking cephalosporin prophylaxis.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…1,2 Frequently, a clinician must prescribe antibiotics empirically for UTIs because antibiotic administration is necessary before the return of urine culture results. Various factors are involved in antibiotic selection for outpatient treatment of UTIs, including patient age, allergies, cost, compliance and dosing frequency, and resistance patterns.…”
mentioning
confidence: 99%
“…During recent years, the third cephalosporins and aminoglycosides are the preferred choice for initial empirical treatment of febrile children suspected with UTI (12,13). In this study, the susceptibility prevalence of E.coli as of most common uropathogens decreased significantly to the tested third cephalosporins and aminoglycosides; P 0.005, 0.000, 0.000, and 0.000 to CTX, CFX, AMK, and GEn respectively.…”
Section: Discussionmentioning
confidence: 52%
“…24 In its practice parameter on febrile UTIs in infants 2 months to 2 years of age, the AAP recommends oral antibiotics for well-appearing children. 25 This recommendation is supported by a recent Cochrane review on the topic, 26 and at least 3 additional trials that have demonstrated that long IV courses do not yield better outcomes than shorter IV courses or oral only courses. [27][28][29] However, all of these trials exclude infants <1 month old, and there are no published recommendations for the <2-month-old age group.…”
Section: Utimentioning
confidence: 99%